Vdelta1 T cells are more resistant than Vdelta2 T cells to the immunosuppressive properties of galectin-3 - Schadeck, Jan; Oberg, Hans-Heinrich; Peipp, Matthias; Hedemann, Nina; Schamel, Wolfgang W.; Bauerschlag, Dirk; Wesch, Daniela (Frontiers in Immunology, 2024)
Ovarian carcinomas have the highest lethality amongst gynecological tumors. A problem after primary resection is the recurrence of epithelial ovarian carcinomas which is often associated with chemotherapy resistance. To improve the clinical outcome, it is of high interest to consider alternative therapy strategies. Due to their pronounced plasticity, γδ T cells are attractive for T-cell-based immunotherapy. However, tumors might escape by the release of lectin galectin-3, which impairs γδ T-cell function. Hence, we tested the effect of galectin-3 on the different γδ T-cell subsets. After coculture between ovarian tumor cells and Vδ1 or Vδ2 T cells enhanced levels of galectin-3 were released. This protein did not affect the cytotoxicity of both γδ T-cell subsets, but differentially influenced the proliferation of the two γδ T-cell subsets. While increased galectin-3 levels and recombinant galectin-3 inhibited the proliferation of Vδ2 T cells, Vδ1 T cells were unaffected. In contrast to Vδ1 T cells, the Vδ2 T cells strongly upregulated the galectin-3 binding partner α3β1integrin after their activation correlating with the immunosuppressive properties of galectin-3. In addition, galectin-3 reduced the effector memory compartment of zoledronate-activated Vδ2 T cells. Therefore, our data suggest that an activation of Vδ1 T-cell proliferation as part of a T-cell-based immunotherapy can be of advantage.